Adoption of Accounting Information Systems on Firm Performance and the Moderating Role of Good Corporate Governance - Jessa Wilsam Putri; Omi Pramiana (Asosiasi Pengelola Publikasi Ilmiah (APPI) PT PGRI, 2025)
This research analyzes the relationship between accounting information system usage and firm performance in manufacturing companies, while considering corporate governance as a moderating factor. The study is based on 240 manufacturing firms listed on the Indonesia Stock Exchange during 2020–2023, with performance measured by Return on Assets (ROA). A quantitative approach is applied using secondary data from financial reports. The analysis employs regression and interaction testing. The findings indicate that greater use of accounting information systems improves firm performance, and this effect becomes stronger when supported by effective corporate governance. These results confirm that organizational performance is shaped by both technological implementation and governance quality.